The Application of Aswaja Values in Everyday Life in the Village of Badransari Punggur, Central Lampung - Banon Ferdiana; Binti Muawanah; Zunita Rachmawati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
This research aims to analyze the application of Ahlus Sunnah Wal Jamaah (Aswaja) values in the daily life of the people of Badransari Village, Punggur, Central Lampung. The method used is a qualitative approach with interviews, observation, and documentation. The results showed that the people of Badransari Village apply Aswaja values in social life, such as inter-religious tolerance, harmony, and moderate worship practices. The application of these values has a positive impact on social harmony and the strengthening of the community's religious identity. This study concludes that strengthening Aswaja values is important to maintain diversity and community harmony.